Studi Hubungan Struktur Mikro dan Keaktifan Zeolit Alam Akibat Proses Pengasaman - Cuaca Vahindra Suriawan, Made; Tirta Nindhia, Tjokorda Gde (Jurnal Energi Dan Manufaktur, 2012)
Natural zeolite is known as metal pollutant adsorbent in industrial waste treatment. As initial study for utilization ofnatural zeolite from Indonesia for metal pollutants adsorbent in liquid waste, then the physical properties should berecognized first. Activation is the first step in order to the natural zeolite able to adsorb the metal pollutants in the waste.One method to activate is by applying acid solution such as sulfuric acid (H2SO4) to activate the natural zeolite. The purposeof this research is to observe the change on microstructure of natural zeolite obtained from the mining at Tasikmalaya, WestJava, Indonesia due to chemical activated, to be compared to one without chemical activation. The variation of concentrationof H2SO4 namely: 2 4 , 6, 8, and 10 % , with 30 minutes soaking time , in a room temperatur. The microstructure then isobserved by using optical microscope following standard for ceramography. The change in microstructure then is analyzedand studied to be related with the ability of natural zeolite in adsorb the metal pollutant. The level activity of the zeolite canbe recognized by measuring its porosity.
Keywords: natural zeolite, activation, sulfuric acid, pollutant, metal